Trail log - 2012 - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2012)
Rolston accounts of Yellowstone wolves, March; Utah Valley University and Bear River Migratory Bird Refuge, April, Socorro isopods (endangered species), Socorro, NM; Rediscovering Aldo Leopold's "Green Fire" site of wolf kill, Apache National Forest, Arizona; July-August; Medicine Bow Mountains, Wyoming, August.